Aspek Yuridis Terhadap Pelaksanaan Pertambangan Rakyat Berdasarkan UU No 4 Tahun 2009 - Muhammad Saleh; Kafrawi -; Abdul Khair (Jatiswara, 2015)
Mining activities in Indonesia obviously have to open a network for remote areas and development activities in accordance with its designation, which leads to the development of new growth centers in some areas. This will encourage and provide benefits in the construction of basic infrastructure for the region, increase revenues, and employment. The business activities of mineral and coal are expected to drive the development of economic empowerment, especially in eastern Indonesia. Development of mineral and coal mining sector should be based on good mining practices and correct by observing the basic elements in accordance with the principles of sustainable development, of the various aspects of life of human beings and other living things in an ecosystem. Artisanal mining management policy carried out by the local government should bersendikan the constitutional mandate that is expected to be as big as possible for improving standards of living for the welfare as well as the objectives of the state. Artisanal mining policy carried out by the local government is not only focused on improving the local economy, but must have meaning and value proportional balance between the growth rate of public welfare with environmental sustainability of the ecosystem. With regard to the mining policy, local government and the parliament as an element of the regional administration has a strategic position and authority in the application of the policy is to create an atmosphere of constructive working relationship in accordance with the mandate of the laws and regulations. The existence of Parliament has a very important position in directing and controlling the various aspects of government policy to play an active role through the functions. Involvement of the oversight function of Parliament against all attitudes / acts carried out by the local government, is an instrument for measuring the basic validity and justification for these policies. With this research is expected to provide an integral understanding of scientific concepts about the functional relationship between the Parliament and Local Government through the oversight function of Parliament in the implementation of mining policy carried out by the people of Local Government. Under the oversight function, the role of Parliament can perform certain actions to steer towards things that should be done as well as control over the circumstances undue occur in any government policy. The method used in this study is a normative method which is based on materials of law and accompanied by field studies as supporting material to the object being studied and analyzed in this study.